Analysis and prediction of space weather events and their impacts on satellite communication systems - Ferreira, Arthur Amaral (2023)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2023.